SEG Technical Program Expanded Abstracts 1984 1984
DOI: 10.1190/1.1893953
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional air gun arrays

Abstract: 02 03 04 05 06 07 08 09 10 11 12 I ! I / 1 \ , I, I, FIG. 4. Signature 33 degrees behind array. Scale factor = 0.495. (Figure 2). The scale factors shown in the figures give the relative amplitude scaling between these three figures. Modeled radiation patternsThere are many parameters that may have an effect on the observed radiation patterns. Some of these are the 2-D array geometry, air gun distribution within the array, variations in the firing times of the air guns, and variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…By deploying each sub-array at a different depth, carefully controlled time delays can be used to build a constructive down-going primary while smearing out the ghost. Smith (1984) introduced a three-dimensional air gun source with four different depths to suppress the source ghost. Using the beam steering approach (Shock 1950), Cambois et al (2009b) studied the multi-level source and presented a case study which demonstrated the effectiveness of improving both low and high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…By deploying each sub-array at a different depth, carefully controlled time delays can be used to build a constructive down-going primary while smearing out the ghost. Smith (1984) introduced a three-dimensional air gun source with four different depths to suppress the source ghost. Using the beam steering approach (Shock 1950), Cambois et al (2009b) studied the multi-level source and presented a case study which demonstrated the effectiveness of improving both low and high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Halliday (2013) compared several source-side deghosting methods by using analytical expressions for the far-fi eld radiation pattern. Smith (1984) presented a three-dimensional airgun source with four different depths to suppress the source ghost. Using the beam-steering approach (Shock, 1950), Cambois et al (2009) studied a multilevel source and presented a case study with two levels to demonstrate the effectiveness of improving the low and high frequencies.…”
Section: Introductionmentioning
confidence: 99%